Кардіоваскулярна автономна нейропатія у хворих на цукровий діабет 2-го типу: особливості змін просторового кута QRS-T, коригованого інтервалу QT і дисперсії інтервалу QT - Сергієнко, В. О.; Сегін, В. Б.; Сергієнко, О. О. (Clinical Endocrinology and Endocrine Surgery, 2012)
The aim of study was to examine the performance characteristics of the spatial angle QRS-T, corrected QT interval and QT interval dispersion in patients with Type 2 diabetes mellitus and cardiovascular autonomic neuropathy (CAN). The study involved 65 patients with Type 2 diabetes mellitus, including 12 patients without verified CVD, 14 patients with subclinical stage CAN, 18 – functional, 21 – functional-organic stage CAN. Control – the state of the studied parameters in 15 healthy people [similar age, body mass index]. It was established, that the increase of the spatial QRS-T angle in patients with Type 2 diabetes mellitus without diagnosed CVD may indicate a presence of subclinical CAN, which often can not be diagnosed using traditional diagnostic methods. Increased parameters of spatial QRS-T angle are correlated with the presence and/or progression of CAN; statistically significantly and independently correlated with prolongation and dispersion of QT interval.